Effectiveness of segmental resection technique in the treatment of placenta accreta spectrum. (2nd October 2021) - Cırpan, Teksin; Akdemir, Ali; Okmen, Fırat; Hortu, Ismet; Ekici, Huseyin; Imamoglu, Metehan
Abstract: Background: Placental accreta is a serious obstetrical entity and its management is challenging. The aim of this study was to evaluate and define our uterus sparing surgical technique in patients with placenta accreta spectrum. Methods: The data of 21 patients who underwent uterine segmental resection during cesarean section with a preliminary diagnosis of placenta accreta spectrum at Ege University between January 2017 and December 2018 were evaluated retrospectively. Results: Twenty-one patients were successfully treated with the segmental resection technique. In all cases, resected tissues were evaluated by histopathologically and the diagnosis of placenta accreta spectrum was confirmed. Hysterectomy was performed in two cases due to peri-partum hemorrhage that disrupted hemodynamics. None of the patients had complications such as visceral organ injury and wound infection. Conclusion: Our technique of uterine sparing surgery seems to be safe and effective in the management of placenta accreta spectrum without increasing complication rates.